Diabetes in ischaemic stroke in a regional Australian hospital: uncharted territory. Issue 4 (13th April 2022) - Hu, Chih‐Chiang; Low, Ashlea; O'Connor, Ellie; Siriratnam, Pakeeran; Hair, Casey; Kraemer, Thomas; Sahathevan, Ramesh
Abstract: Background: Stroke and diabetes mellitus (DM) are significant interrelated healthcare issues but there is a dearth of data on the prevalence of DM among Australia's regional stroke population. Aims: We aimed to determine the prevalence of DM in stroke patients at a large regional centre, including subanalyses on stroke subtypes, glycaemic control and renal function in ischaemic stroke (IS). Methods: We conducted a retrospective analysis of all patients ( n = 323) with IS or transient ischaemic attack (TIA) admitted to Ballarat Base Hospital from January 2015 to December 2016. Demographic data, cardiovascular risk factors, aetiology/territory of IS, pre‐morbid DM status, indicators of glycaemic control and renal impairment were recorded. Results: DM was present in 28.5% of IS and TIA patients, including 4% being newly diagnosed. Among diabetic IS patients, 45.3% had poor glycaemic control (HbA1c ≥7.0%) while 16% had moderate to severe renal impairment (estimated glomerular filtration rate of <30). The majority of IS were partial anterior circulation stroke (53.4%) and cardioembolism was the commonest mechanism (43.5%). We found no significant association between DM and a specific stroke location or mechanism. Conclusions: Almost one‐third of IS/TIA patients had DM, with a significant proportion showing poor glycaemic control. The DM prevalence in our cohort was comparable with reported rates from other developed countries. Although we found no association between DM and a particular stroke type or mechanism, it is likely a reflection of our cohort size. Our study demonstrated that DM, as a significant risk factor in IS, warrants early detection and better management strategies.